Discovery of new Schiff bases of the disalicylic acid scaffold as DNA gyrase and topoisomerase IV inhibitors endowed with antibacterial properties - Al-Wahaibi, Lamya H.; Mahmoud, Mohamed A.; Alzahrani, Hayat Ali; Abou-Zied, Hesham A.; Gomaa, Hesham A. M.; Youssif, Bahaa G. M.; Bräse, Stefan; Rabea, Safwat M. (Frontiers in Chemistry, 2024)
DNA gyrase and topoisomerase IV show great potential as targets for antibacterial medicines. In recent decades, various categories of small molecule inhibitors have been identified; however, none have been effective in the market. For the first time, we developed a series of disalicylic acid methylene/Schiff bases hybrids (5a-k) to act as antibacterial agents targeting DNA gyrase and topoisomerase IV. The findings indicated that the new targets 5f-k exhibited significant antibacterial activity against Gram-positive and Gram-negative bacteria, with efficacy ranging from 75% to 115% of the standard ciprofloxacin levels. Compound 5h demonstrated the greatest efficacy compared to the other compounds tested, with minimum inhibitory concentration (MIC) values of 0.030, 0.065, and 0.060 µg/mL against S. aureus, E. coli, and P. aeruginosa. 5h had a MIC value of 0.050 µg/mL against B. subtilis, which is five times less potent than ciprofloxacin.The inhibitory efficacy of the most potent antibacterial derivatives 5f, 5h, 5i, and 5k against E. coli DNA gyrase was assessed. The tested compounds demonstrated inhibitory effects on E. coli DNA gyrase, with IC50 values ranging from 92 to 112 nM. These results indicate that 5f, 5h, 5i, and 5k are more effective than the reference novobiocin, which had an IC50 value of 170 nM.Compounds 5f, 5h, 5i, and 5k were subjected to additional assessment against E. coli topoisomerase IV. Compounds 5h and 5i, which have the highest efficacy in inhibiting E. coli gyrase, also demonstrated promising effects on topoisomerase IV. Compounds 5h and 5i exhibit IC50 values of 3.50 µM and 5.80 µM, respectively. These results are much lower and more potent than novobiocin's IC50 value of 11 µM. Docking studies demonstrate the potential of compound 5h as an effective dual inhibitor against E. coli DNA gyrase and topoisomerase IV, with ADMET analysis indicating promising pharmacokinetic profiles for antibacterial drug development.